EVALUASI SISTEM ADMINISTRASI PENGAJARAN, PENELITIAN DAN PENGABDIAN PADA MASYARAKAT MENYONGSONG ERA INDUSTRI 4.0 DI STIT RADEN WIJAYA MOJOKERTO - Arief, Mochamad Budi (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2018)
The role of information technology in teaching, research and administration is that we are aware of the strategic tool for institutions. Data works using digital technology and digital systems is an integral part of teaching administration, research and community service in higher education. Educational institutions are often driven by political and contextual considerations, not evidence of pedagogical impacts. By utilizing the professional experience of college innovators and many international case studies, practical all aspects of university advice and guidance on university management is an interesting, comprehensive and easily accessible practical guide, from culture to university and the role it plays, to providing leadership effective and manage change. At STIT Raden Wijaya Mojokerto. This is a system of teaching, research and community service to meet the industrial era. 1) The availability of abundant information, advanced technology, and rapidly changing societies, greater convenience in the daily life of the capital must reform the education system as the core of international competition, education is developed students to develop student learning and undergraduate education, improving learning environments, and increasing teacher training, transforming learning environments into purposeful, generative learning, attentive learning, and results-based learning. 2) Given the diverse learning needs and involvement of diverse student populations, the institution needs to develop skills with a flexible approach to teaching important to improve student success. Professional development provides exposure to effective evidence-based teaching strategies in online contexts, can improve their teaching practices. 3) Supporting refills and patches reform strategies to improve digital status. While the development of digital technology provides cheap resources for educational practices, this can be done by raising reformist leadership, initiators and strategic planners, supported leadership. building collaborative supported pedagogical systems and learning support organizations and helping teachers develop four new roles: learners, facilitators for student-centered learning, collaborators and researchers.